KIMURA'S DISEASE: A DIAGNOSTIC CHALLENGE - MAHESH KUMAR U; YELIKAR BR. (International Journal of Pharma and Bio Sciences, 2012)
Kimura’s disease (KD) is a relatively uncommon chronic inflammatory condition that appears to represent an unusual allergic or autoimmune response. It is extremely uncommon in Indian subcontinent. This case is being presented to make clinicians and ENT surgeons aware of Kimura’s disease as a differential diagnosis of swelling in head and neck region, because these are frequently misdiagnosed as angiolymphoid hyperplasia with eosinophilia, Hodgkin’s lymphoma, castleman’s disease, angioma, lymphangioma or haemangioma.